2009
DOI: 10.1159/000229531
|View full text |Cite
|
Sign up to set email alerts
|

Does Center Volume Correlate with Survival from Breast Cancer?

Abstract: Key WordsBreast cancer · Caseload · Survival · Specialization Summary With its high incidence and long history of patient advocacy, breast cancer has generated the most concern about the quality of its care and the volume-outcome relationship. In breast cancer surgery, the risk of perioperative morbidity or mortality is low, but surgery is only one single piece in the mosaic of multidisciplinary care that eventually determines survival. Only a limited number of articles is available investigating the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…53 The association between higher surgeon case load and higher survival found both in the unadjusted analysis and the analysis adjusted for age and clinical risk factors, accords with results of most studies in North America, Europe, Asia and Western Australia. 16,[28][29][30][31][32][33][34][35][36][37][38][39][40] The difference mostly occurred between 21-100 cases per annum and lower case loads, with little difference observed between the 21-100 and higher case loads. Other studies have shown a progressive association between higher case loads and survival, interpreted by some researchers as strengthening evidence of a causal relationship.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…53 The association between higher surgeon case load and higher survival found both in the unadjusted analysis and the analysis adjusted for age and clinical risk factors, accords with results of most studies in North America, Europe, Asia and Western Australia. 16,[28][29][30][31][32][33][34][35][36][37][38][39][40] The difference mostly occurred between 21-100 cases per annum and lower case loads, with little difference observed between the 21-100 and higher case loads. Other studies have shown a progressive association between higher case loads and survival, interpreted by some researchers as strengthening evidence of a causal relationship.…”
Section: Discussionmentioning
confidence: 94%
“…This was similar to classifications in some other studies, although classification categories have not been consistent across studies. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] Treatment centre location was categorised as major city, inner regional or more remote, using the Australian Standard Geographical Classification. 44 These categories are based on Census Collection Districts (CDs) categorised using the Accessibility/Remoteness Index for Australia (ARIA), which is a measure of the remoteness of a location from the services provided by large towns or cities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors Scharl and Göhring discuss the correlation between minimal numbers and course of disease [4]. For the criterion of minimal numbers, it is important to know which parameters are being used.…”
Section: Minimal Numbers -Center Volume and Interdisciplinaritymentioning
confidence: 99%